Effect of Religious Coping Skills Training on Modifying Metacognitive Beliefs among Children of Veterans with PTSD - B. Ali Gouhari; Kh. Abolmaali Alhosseini; F. Dortaj; F. Jomehri (Afarand Scholarly Publishing Institute, 2020)
Aims: Defect in metacognitive beliefs increases the vulnerability of children of veterans with post-traumatic stress disorder (PTSD) to mental health problems. The purpose of this study was to determine the effect of religious coping skills training on modifying metacognitive beliefs among children of veterans with PTSD. Materials & Methods: This semi-experimental study with pretest-posttest design with control group and one- month follow-up was conducted among 20 Shahed students (the children of veterans with PTSD) in Islamic Azad University-Roudehen Branch in 2016. The subjects were selected by purposive sampling method and randomly assigned to control and experimental groups (10 people in each group). The experimental group received 10 sessions of religious coping skills training and the control group did not receive training during this period. Both groups completed the metacognitions questionnaire (MCQ-30), before, after, and one month after the intervention. Data were analyzed by SPSS 22 software using multivariate analysis of variance. Findings: In post-test step, only the components of positive beliefs about worry (F=3.511; p=0.045) and cognitive self-consciousness (F=6.482; p=0.008) were significantly different between the two groups. In the follow-up step, there was still a significant difference between the two control and experiment groups in terms of positive beliefs about worry (F=5.134; p=0.001) and cognitive self-consciousness (F=6.956; p=0.001). Conclusion: The religious coping skills training improves some of the components of metacognitive beliefs that is, positive beliefs about worry and lack of cognitive self-consciousness that its effect persists after one month.